A study on the factors influencing the effectiveness of Celcom’s brand equity strategy / Balqis Mohamad Daing - Mohamad Daing, Balqis (2011)
The aim of this study was to examine the factors that the effectiveness of Celcom’s brand equity strategy. There are three factors being studied, which were: perceived quality, marketing efficiency and brand awareness. As Celcom Company had been chosen as the unit of analysis for this study, the researcher is also interested to know about the performance and effectiveness of Celcom’s brand equity strategy. In collecting data, the researcher used both secondary and primary data. Moreover, questionnaires had been used in order to get feedback from the consumers. The researcher had distributed 100 questionnaires and had gotten back 100 respondents’ feedback. The data collected was then tested on its reliability, and then further analyzed using frequency analysis and Pearson Correlation Coefficient. Besides, Regression Analysis was used to test the hypotheses in this study. The findings of this paper suggest that all the factors are significant factors in explaining the effectiveness of Celcom’s brand equity strategy. Based from the results obtained in this study, the researcher suggests some recommendations that can help Celcom Company to improve brand equity strategy and increase the numbers of sales and consumers also reduce the complaints from consumers